GENDER REPRESENTATIONS AND STEREOTYPES IN SINGAPOREAN PICTURE BOOKS: 1970 TO 2008 - Luyt, Brendan; Seng, Sheh Lee; Ng, Yung Yong (Malaysian Journal of Library and Information Science, 2017)
Research done in other countries has found that picture books under-represent females and contain gender stereotypes. Little research exists for the case of picture books published by Singaporean authors. Using a content analysis approach a random sample of 80 Singaporean picture books published from the 1970s to the present was coded. In particular the following elements were examined: male and female names in book titles and of main characters, male and female illustrations, and portrayal of males and females in outdoor and indoor scenes. The findings show that by the 2000s rough gender parity had been attained with one key finding being that the 1980s was a pivotal turning-point in the representation of gender. Two potential explanations are provided for why this might be so.